Echocardiography in the diagnostic evaluation and phenotyping of heart failure with preserved ejection fraction. Issue 6 (June 2022) - Harada, Tomonari; Kagami, Kazuki; Kato, Toshimitsu; Obokata, Masaru
Highlights: The demonstration of elevated left ventricular (LV) filling pressure, in which echocardiography plays a central role, is crucial in diagnosing heart failure with preserved ejection fraction (HFpEF) in euvolemic patients with dyspnea. Exercise stress echocardiography may enhance the diagnosis of HFpEF by detecting elevation in LV filling pressures that develop only during exercise. Echocardiography also provides valuable insight into the pathophysiology and underlying phenotypes of HFpEF. Exercise stress echocardiography may allow for a better pathophysiological characterization in HFpEF. Abstract: Heart failure with preserved ejection fraction (HFpEF) represents one of the greatest unmet needs in modern cardiology given its diagnostic difficulty and limited therapeutic options. Echocardiography provides valuable information on cardiac structure, function, and hemodynamics and plays a central role in the evaluation of HFpEF. Echocardiography is crucial in identifying HFpEF among patients with dyspnea, especially when overt congestion is absent. The combination of echocardiographic indices of diastolic function, clinical characteristics, and natriuretic peptide tests has been proposed in the diagnostic evaluation of patients with suspected HFpEF. Echocardiography also provides valuable insight into the pathophysiology and underlying phenotypes of HFpEF. Exercise stress echocardiography can also detect abnormalities that develop only during exercise. This may enhance the diagnosis of HFpEF by demonstrating elevation in the left ventricular filling pressure and may have potential for better pathophysiological characterization. This review focuses on the role of echocardiography in the diagnostic evaluation and phenotyping of HFpEF. We also discuss the potential role of exercise stress echocardiography for the diagnosis and disease phenotyping of HFpEF. Graphical abstract: Image, graphical abstract